2016
DOI: 10.1002/ange.201610836
|View full text |Cite
|
Sign up to set email alerts
|

Native Top‐Down Mass Spectrometry of TAR RNA in Complexes with a Wild‐Type tat Peptide for Binding Site Mapping

Abstract: Ribonucleic acids (RNA) frequently associate with proteins in many biological processes to form more or less stable complex structures.T he characterization of RNAprotein complex structures and binding interfaces by nuclear magnetic resonance (NMR) spectroscopy, X-rayc rystallography,orstrategies based on chemical crosslinking,however,can be quite challenging.H erein, we have explored the use of an alternative method, native top-down mass spectrometry (MS), for probing of complex stoichiometry and protein bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Tandem MS of protein-nucleic acid complexes has recently showed progress to address complexes of larger DNA/RNA molecules, beyond the earlier work with single nucleotides [23, 49]. The sites of peptide binding to a 31-nucleotide sequence of TAR RNA were recently elucidated by native top-down MS [50]. As larger protein-nucleic acid complexes are probed by native top-down MS, better models will be needed to help us better understand the dissociation process of complexes composed of large, highly negatively charged molecules bound to proteins [51].…”
Section: Discussionmentioning
confidence: 99%
“…Tandem MS of protein-nucleic acid complexes has recently showed progress to address complexes of larger DNA/RNA molecules, beyond the earlier work with single nucleotides [23, 49]. The sites of peptide binding to a 31-nucleotide sequence of TAR RNA were recently elucidated by native top-down MS [50]. As larger protein-nucleic acid complexes are probed by native top-down MS, better models will be needed to help us better understand the dissociation process of complexes composed of large, highly negatively charged molecules bound to proteins [51].…”
Section: Discussionmentioning
confidence: 99%
“…165 Schneeberger and Breuker have used CID to determine the binding site of RNA on proteins, again taking advantage of the strengthening in the gas phase of electrostatic interactions to the point where they are occasionally able to survive backbone fragmentation. 166 Recently, O'Connor and coworkers have shown that ECD fragmentation of oligomers of the amyloidogenic peptide amylin (implicated in type 2 diabetes) can provide information on the binding interface between monomers (see Fig. 6).…”
Section: Native Mass Spectrometry Of Protein Complexesmentioning
confidence: 99%
“…To gain insight into the biochemistry of retroviruses and further antiviral drug development, atomic-level details of RNA-protein complex structures and their binding interfaces can be studied by nuclear magnetic resonance (NMR) spectroscopy or X-ray crystallography. An emerging alternative that can complement these techniques, especially when RNAprotein complexes show unfavorable conformational dynamics that complicate NMR data interpretation 2,3 or fail to crystallize properly 4,5 , is native top-down mass spectrometry (MS) 6 . We have recently demonstrated that native electrospray ionization (ESI) [7][8][9][10][11][12] provides time-resolved, stoichiometric information on complexes of transactivation responsive (TAR) RNA and transactivating (tat) peptide from human immunodeficiency virus type 1 (HIV-1), and that collisionally activated dissociation (CAD) can reveal tat binding sites of TAR RNA at the single-nucleotide level 6 .…”
mentioning
confidence: 99%
“…An emerging alternative that can complement these techniques, especially when RNAprotein complexes show unfavorable conformational dynamics that complicate NMR data interpretation 2,3 or fail to crystallize properly 4,5 , is native top-down mass spectrometry (MS) 6 . We have recently demonstrated that native electrospray ionization (ESI) [7][8][9][10][11][12] provides time-resolved, stoichiometric information on complexes of transactivation responsive (TAR) RNA and transactivating (tat) peptide from human immunodeficiency virus type 1 (HIV-1), and that collisionally activated dissociation (CAD) can reveal tat binding sites of TAR RNA at the single-nucleotide level 6 . This native top-down MS approach relies on the preservation of electrostatic interactions between protonated peptides and deprotonated RNA at energies that are sufficiently high for phosphodiester backbone bond cleavage 6 , for which as few as two arginine residues are sufficient 13 .…”
mentioning
confidence: 99%